2021
DOI: 10.1038/s41467-021-25460-3
|View full text |Cite
|
Sign up to set email alerts
|

Opposing roles for striatonigral and striatopallidal neurons in dorsolateral striatum in consolidating new instrumental actions

Abstract: Comparatively little is known about how new instrumental actions are encoded in the brain. Using whole-brain c-Fos mapping, we show that neural activity is increased in the anterior dorsolateral striatum (aDLS) of mice that successfully learn a new lever-press response to earn food rewards. Post-learning chemogenetic inhibition of aDLS disrupts consolidation of the new instrumental response. Similarly, post-learning infusion of the protein synthesis inhibitor anisomycin into the aDLS disrupts consolidation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 65 publications
3
19
0
Order By: Relevance
“…Focusing on detailed aspects of instrumental behavior offers potential avenues for providing a thorough characterization of the role of nucleus accumben and its DA innvervation in regulating motivated behavior. Smith et al (2021) reported that while inhibition of protein synthesis in nucleus accumbens by local injections of anisomycin did not affect the learning of a new instrumental response, post-learning intra-accumbens infusions of anisomycin did reduce the vigor of executing the response, which was reflected by the reduced number of responses within bouts of lever pressing (i.e., bout density). This is important because bout density is thought to be a marker of response to increasing effort requirements in lever pressing.…”
Section: Levels Of Da Transmission Exert a Bi-directional Modulation ...mentioning
confidence: 99%
“…Focusing on detailed aspects of instrumental behavior offers potential avenues for providing a thorough characterization of the role of nucleus accumben and its DA innvervation in regulating motivated behavior. Smith et al (2021) reported that while inhibition of protein synthesis in nucleus accumbens by local injections of anisomycin did not affect the learning of a new instrumental response, post-learning intra-accumbens infusions of anisomycin did reduce the vigor of executing the response, which was reflected by the reduced number of responses within bouts of lever pressing (i.e., bout density). This is important because bout density is thought to be a marker of response to increasing effort requirements in lever pressing.…”
Section: Levels Of Da Transmission Exert a Bi-directional Modulation ...mentioning
confidence: 99%
“…We therefore defined bout-initiating presses as those occurring at least 2.5 s after the last press, to avoid misclassifying withinbout presses. Previous studies have used similar cut-off values 10.3389/fnbeh.2022.999320 (Reed, 2011;Wassum et al, 2013;Smith et al, 2021) and indicate that such bout analyses are robust to variation in this parameter (Mellgren and Elsmore, 1991;Shull et al, 2002). Presses that occurred within 2.5 s of a food-port entry (Figures 2C,D and Entry-Press), regardless of the timing of the last lever press, were also categorized as bout-initiating presses as they represent a return to instrumental reward-seeking behavior.…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, these MSNs receive convergent excitatory inputs from the cortical and thalamic areas and further project to the output nuclei of the basal ganglia circuit [ 115 ]. In addition, Drd2+ MSNs have been shown to be crucial in habit formation in mice [ 116 , 117 ]. This is particularly interesting because both from a cognitive-behavioral and neuroscientific perspective, tics—the hallmark of TD—can be viewed as habits that have been formed over time and that are associated with premonitory sensations and can, at least partially, be controlled [ 118 , 119 , 120 , 121 , 122 ].…”
Section: Discussionmentioning
confidence: 99%